2015
DOI: 10.1099/vir.0.000034
|View full text |Cite
|
Sign up to set email alerts
|

Definition of herpes simplex virus helper functions for the replication of adeno-associated virus type 5

Abstract: Adeno-associated virus (AAV) type 5 represents the genetically most distant AAV serotype and the only one isolated directly from human tissue. Seroepidemiological evidence suggests herpes simplex virus (HSV) as a helper virus for human AAV5 infections, underlining the in vivo relevance of the AAV-herpesvirus relationship. In this study we analysed, for the first time, HSV helper functions for productive AAV5 replication, and compared these to AAV2. Using a combination of HSV strains and plasmids for individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Although most studies have focused on HSV-1 and AAV2 coinfections, it is likely that the same HSV-1 factors also support the replication of other AAV serotypes. A study by Stutika et al analyzed HSV-1 helper factors supporting AAV5 replication and concluded that the previously revealed helper functions for AAV2 also apply to AAV5 [ 150 ]. Since AAV5 is the most distantly related strain of AAV and was, in contrast to AAV1–4, directly isolated from human tissue, it is likely that the same HSV-1 factors, which support AAV2 and AAV5 replication, also support other AAV serotypes [ 151 , 152 ].…”
Section: Helper Viruses and Aavmentioning
confidence: 99%
“…Although most studies have focused on HSV-1 and AAV2 coinfections, it is likely that the same HSV-1 factors also support the replication of other AAV serotypes. A study by Stutika et al analyzed HSV-1 helper factors supporting AAV5 replication and concluded that the previously revealed helper functions for AAV2 also apply to AAV5 [ 150 ]. Since AAV5 is the most distantly related strain of AAV and was, in contrast to AAV1–4, directly isolated from human tissue, it is likely that the same HSV-1 factors, which support AAV2 and AAV5 replication, also support other AAV serotypes [ 151 , 152 ].…”
Section: Helper Viruses and Aavmentioning
confidence: 99%
“…HeLa cells seeded at a density of 30% were infected 20 h later with AAV2 wild-type or AAV-A1 mutant (multiplicity of infection [MOI] 250) and/or Ad2 (MOI 25). Transfection of HeLa cells with AAV plasmids was performed as described previously (21). Infection with Ad2 (MOI 25) was performed 16 h post- …”
Section: Methodsmentioning
confidence: 99%
“…Light green circles mark GFP-labeled structures by H8 tracer at both 36 hpi and 48 hpi; dark green circles mark GFP-labeled structures at 48 hpi can be directly used by AAV for its efficient replication and packaging. The required HSV genes for AAV production include UL5, UL8, UL9, UL29, UL30, UL42, and UL52, all of which are components of the HSV core replication system [35,36].…”
Section: Discussionmentioning
confidence: 99%